Ensaios biológicos para avaliação de segurança de produtos cosméticos - Chorilli, Marlus [UNESP]; Tamascia, P.; Rossim, C.; Salgado, Hérida Regina Nunes [UNESP] (My University, 2009)
Despite efforts to the contrary, some cosmetic products can cause undesirable side effects in the users. These may often be due to individual factors or inappropriate use of the product. Thus, biological assays to assess the safety of a new cosmetic must precede its being placed on the market. Historically, these tests have always been carried out in vivo, in animals, since such tests can be used to evaluate many of the potential risks, such as irritation, allergy or systemic effects; but, recently, some research centers have been adopting in vitro alternatives, in order to replace the animal tests. This review emphasizes the need to employ biological assays to test the safety of cosmetic products, and reviews the main in vivo and in vitro tests used, focusing on the need to develop and use alternatives to the in vivo assays of product safety, so as to offer the consumers the maximum safety with the least possible risk, while ensuring the best conditions of use of the product.

Apesar de não ser desejável, alguns produtos cosméticos podem apresentar reações adversas aos usuários. Tais efeitos, muitas vezes, podem ser decorrentes de fatores individuais ou até mesmo pelo uso inadequado do produto. Logo, os ensaios biológicos para avaliação de segurança devem preceder a colocação do cosmético no mercado. Historicamente, estes ensaios sempre foram realizados in vivo, em animais, uma vez que podem ser utilizados para avaliar grande parte dos riscos potenciais envolvidos, seja irritação, alergia ou efeitos sistêmicos; todavia, atualmente alguns centros de pesquisa estão adotando alternativas in vitro aos ensaios com animais. Esta revisão enfatiza a necessidade de realização de ensaios biológicos para avaliação de segurança de produtos cosméticos, bem como apresenta os principais testes in vivo e in vitro empregados, abordando a necessidade de aplicar-se métodos alternativos aos ensaios in vivo na avaliação de segurança dos mesmos, de forma a oferecer aos consumidores o máximo de segurança com o menor risco, garantindo as melhores condições de uso do produto. Palavras-chave: Ensaios biológicos. Avaliação de segurança. Produtos cosméticos.
Biological assays for evaluate the safety of cosmetic products
Keywords: Biological assays; Cosmetic products; Safety evaluation; cosmetic; acne; animal experiment; animal model; bioassay; comedo; consumer; cytotoxicity; in vitro study; in vivo study; nonhuman; phototoxicity; review; risk; safety